A Comparative Study on the Nonlinear Control of Ball and Plate - Sen, Busra; Turke, Turker (IEEE, 2018)
Two different nonlinear controller design techniques are presented and compared for ball and plate system. Firstly, a cascaded controller is designed consisting of inner and outer loop controllers separately. In this design procedure, the inner loop controller provides the tracking of a trajectory by the plate while the outer loop controller generates the reference trajectory for the plate with respect to the command input for the ball. Secondly, a backstepping controller is developed for the same system. Linear dynamics is obtained in the closed loop system with both of the control structures. Finally, numerical simulations are implemented for different reference signals with controller gains providing the closed loop dynamics having the same eigenvalues for both of the designed controllers, and the responses are compared comprehensively.
Keywords: Ball and plate; backstepping; nonlinear control; DISTURBANCE REJECTION; TRACKING; Automation & Control Systems; Engineering; Robotics